Dietary Intake of Advanced Glycation End Products Did Not Affect Endothelial Function and Inflammation in Healthy Adults in a Randomized Controlled Trial. Issue 7 (17th April 2014) - Semba, Richard D.; Gebauer, Sarah K.; Baer, David J.; Sun, Kai; Turner, Randi; Silber, Harry A.; Talegawkar, Sameera; Ferrucci, Luigi; Novotny, Janet A.
Abstract: When food is heated to high temperatures, the characteristic "browning" generates advanced glycation end products (AGEs). AGEs are associated with an increased risk of cardiovascular disease, diabetes, and other adverse outcomes. Whether dietary AGEs are absorbed and are harmful to human health remains highly controversial. The objective of this study was to compare the effects of a diet high or low in AGEs on endothelial function, circulating AGEs, inflammatory mediators, and circulating receptors for AGEs in healthy adults. A randomized, parallel-arm, controlled dietary intervention was conducted for 6 wk with 24 healthy adults, aged 50–69 y, that compared isocaloric, food-equivalent diets that were prepared at either high or mild temperatures. Peripheral arterial tonometry, serum and urine carboxymethyl-lysine (CML), inflammatory mediators (interleukin-6, C-reactive protein, vascular adhesion molecule-1, and tumor necrosis factor-α receptors I and II), soluble receptor for AGEs, and endogenous secretory receptor for AGEs were measured at baseline and after 6 wk of dietary intervention. In the low-AGE diet group, the following changed from baseline to 6 wk (mean ± SE): serum CML from 763 ± 24 to 679 ± 29 ng/mL ( P = 0.03) and urine CML from 1.37 ± 1.47 to 0.77 ± 2.01 μg/mL creatinine ( P = 0.02). There were no significant changes in serum and urinary CML concentrations from baseline to follow-up in the high-AGE diet group. A high- or low-AGE diet had no significant impact on peripheral arterial tonometry or any inflammatory mediators after 6 wk of dietary intervention. In healthy middle-aged to older adults, consumption of a diet high or low in AGEs for 6 wk had no impact on endothelial function and inflammatory mediators, 2 precursors of cardiovascular disease. This trial was registered at clinicaltrials.gov as NCT01402973.